The Second Semester Students' Communication Apprehension in Learning English as Foreign Language at PGRI Silampari University: Introduction: Types of Communication Apprehension, Factors of Communication Apprehension. Research method, findings and discussion, conclusion and suggestions - Ayu Oktaviani; Pransiska, Ayu; Hamdan (Universitas Islam Lamongan, 2024)
The aimed of this research to find out what were the types of second semester students’ communication apprehension and to find out the factors of second semester students’ communication apprehension in learning English as foreign language at PGRI Silampari University. The researchers used descriptive qualitative method and data collection was done through observation checklist and interview. The research involved 23 students of second semester English Education study program at PGRI Silampari University. The results showed that students communication apprehension experienced trait-like, context-based, audience-based and situational of CA. the factors of students’ communication apprehension in learning English as foreign language were nervous, lack of vocabulary, not confident, shy or embarrassed, afraid making mistakes, not comfortable with the situations, insecure and afraid for bad judgement or negative evaluation from others. In addition, the conclusion of this research were mostly students experienced trait-like and situational of CA and the factors students experiencing both types were due to nervous, lack of vocabulary, afraid making mistakes and afraid for negative evaluation or bad judgement.